Faktor yang Mempengaruhi Perilaku Ibu Terhadap Pemenuhan Imunisasi Dasar Anak di Desa Matang Baroh - Pasyame Rembune Kala; Quranayati Quranayati; Mansura Feby Amanda; Rifka Annida (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Basic immunization is one of the prevention programs for communicable diseases to children. Immunization coverage rates in regions have not yet reached the target. This is caused by many factors. This study aimedto analyze factorsthatinfluencingto maternal behavior in fulfilling basic immunization for children aged 0-12 months in the Work Areaof the Sumobito Health Center in Jombang.The factors analyzed are not only internal factors of the individual, but also external factors, both family environment and the availability ofservices, whichare also determinants ofbehavior.This research was observational analytic with cross sectional approach. Data analysis used logistic regressiontest. The results of this study indicated that factorsinfluencedmaternal behavior in fulfilling childbasic immunization wereattitude (p = 0,000), trust (p = 0,002), family support (p = 0.006), access (p = 0,000), and information (p=0,000), while age (0,718) and work status (0,844) did not influence to maternal behavior in fulfilling child basic immunizationThis is because, during the COVID-19 pandemic, mothers worked at home so they had time to deliver their children to immunization